Modulating Effects of L-Arginine and Tribulus terrestris Extract on Fipronil-Induced Interference in the Male Reproductive System of Rats: Antioxidant Potential, Androgen Receptors, and Nitric Oxide Synthase Interplay - Doaa H. Elsayed; Ahmed A. Bakhashwain; Eman A. Ahmed; Hatim A. Al-Abbadi; Heba M. A. Abdelrazek; Menna Allah I. El-Menyawy; Wafaa K. Teleb; Noran M. Tawfik; Ibrahim E. Helal; Heba N. Gad EL-Hak (Toxics)
The protective potentials of Tribulus terrestris (TT) and L-arginine (L-Arg) against reproductive toxicity induced by fipronil (FPN) in male rats were investigated. A total of 36 male rats were allocated into six groups: control, TT, L-Arg, FPN, FPN + TT, and FPN + L-Arg groups. The body and sex organ weights, semen criteria, serum testosterone levels, and testicular oxidative stress were determined. Sexual behavior, testicular and penile androgen receptor (AR), penile nitric oxide synthase (NOS), immunohistochemistry of proliferating cell nuclear antigen (PCNA), and histopathology were also assessed. FPN disrupted reproductive health by influencing the expression and activity of NOS and AR, leading to compromised erectile function, sexual dysfunction, and hormonal imbalance. Significant improvements in body weight, reproductive organ weights, the expression of NOS and AR, and testosterone levels were observed in the TT- and L-Arg-treated groups. Behavioral assessments indicated improved sexual performance in the TT- and L-Arg-treated groups. Histopathological studies of the testes and penis tissue, immunohistochemical expression of PCNA in testicular tissues, and biochemical analyses further confirmed the protective effects of TT and L-Arg. Collectively, these findings highlighted the potential of TT and L-Arg in counteracting FPN-induced reproductive impairments.